Positive Image of the USSR and Soviet Characters in American Films in 1943-1945 - Alexander Fedorov (Centre for Behaviour and Wellness Advocacy, 2014)
In the article the author performs a hermeneutic analysis of cultural context, i.e. investigation of media texts interpretation, cultural and historical factors influencing the views of the agency / author of a media text and the audience, on specific examples of positive image of the USSR and soviet characters in American films in 1943-1945. The author bears in mind that the hermeneutic analysis of a media text comprehension involves a comparison with a historical, cultural tradition and reality; insight into its logic; comparison of media images in historical and cultural contexts combined with the historical, hermeneutical analyses of the structural, plot, ethical, ideological and iconographic / visual analyses of media stereotypes and media text characters. The analysis of these media texts, in the author's opinion, is especially important for media education of future historians, culture experts, art critics, social scientists, philologists, psychologists and teachers.